Studi Penentuan Volume Stockpile Penambangan Bijih Nikel Menggunakan Foto Drone - Muhammad Fathurrahman; L.M Golok Jaya; Fitra Saleh; Fitrani Amin; Al Amin Siharis (Universitas Halu Oleo, 2023)
UAV drones can yield differences in volume compared to the actual volume in stockpile volume calculations when compared to measurements obtained using a Total Station. The measurement method using drone photos can streamline labor compared to Total Station utilities, with both utilizing processed data in the form of point clouds. This research aims to: (1) Determine nickel stockpile volumes using drone photos; (2) Compare volume between drone photos and Total Station. Parameters encompass flight height, drone speed, overlap, and camera angle. Stockpile volumes are calculated using methods Extended Trapezoidal Rule. Research outcomes include: (1) Determination of stockpile volumes using drones is feasible through photogrammetry with Struktur torm motiontechniques; (2) Volume accuracy using Extended Trapezoidal Rule method is 0.033% for dome 1, 0.833% for dome 2, 0.415% for dome 3, 0.298% for dome 4, 0.242% for dome 5, 0.007% for dome 6.